Conservation of ecosystem services in high-altitude Andean wetlands: social participation in the creation of a natural protected area. - Rubio, María Clara (2017)
The goal of the present work is synthesizing the process of collective construction developed to protect the high-altitude wetlands of the Blanco River basin, located in the Andes Mountains, Mendoza province. The participatory process arose out of an initiative of basin residents and users, and was conducted by the Integrative Committee for Creation of Potrerillos Municipal Environmental Protected Area (MEPA), composed of civil society organizations, government agencies and scientific institutions. The major pressures affecting the wetlands, identified through participatory assessment of the socio-ecosystem are: water pollution, reduction and total loss of habitat, stoppage of of groundwater flows, artificial drainage, poldering of the meadow, and fragmentation of the wetland system, among other pressures.In order to identify priority sites for conservation of the ecosystem services (ES) wetlands provide, local people identified and prioritized the six most important of them according to their perception: water for human consumption, agriculture and industry; aesthetic, spiritual and non-use representations; recreation and ecotourism; erosion control; water regulation and regulation of the biotic environment. The areas supplying ES were identified on the map of land use and land cover of the basin, with the wetland area, with tourist use and water catchment, and the watershed?s headwaters standing out as areas with higher ES provision. This process culminated in the creation of a protected area to halt the intense degradation affecting the wetland system, promoting maintenance of the natural area and improving its provision of ES. This collective process allowed integrating local and scientific knowledge, becoming an experience to be replicated in other areas in terms of conservation and land management. Among its major strengths is a strong coordination between the different social actors involved, which allowed success in reaching the implementation stage of a public policy for conservation.